DEVELOPMENT OF FLOOD DISASTER MITIGATION LEARNING MODEL IN EARLY CHILDHOOD EDUCATION - Celia Cinantya; Mohammad Dani Wahyudi; Maimunah Maimunah (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2021)
This study aims to develop a learning model for flood disaster mitigation in Early Childhood. The research method used is the Research and Development (RD) method. The research was carried out in several stages. The first stage, conducting a preliminary study and needs analysis (early data collection); the second stage, planning; The third stage, the development of the draft product in this case the Daily Lesson Plan development flood disaster mitigation, the fourth stage is the validation and trial stage. Based on research results, it was found that the development of the flood disaster mitigation learning model met the valid criteria of 3.50, 98% effective and practical test of 3.9 in learning flood disaster mitigation in early childhood. Thus, it can be concluded that the flood disaster mitigation model can be used for learning activities to introduce the concept of science and the concept of environmental care in Early Childhood, especially for children aged 4-6 years. The finding or novelty element in this study is the design of the flood disaster mitigation learning model is easier for children to understand, because the implementation of the model has been adapted to the characteristics and uses learning methods and approaches that are appropriate to the stages of development based on age levels.